The Concept of Tension between Law and Pre-Reflexive Freedom - Dingilevskis, Marijus (Teisė, 2024)
By using the method of phenomenological analysis, the article analyses the relationship between pre-reflexive freedom (spontaneous, impulsive, emotional), which is contrasted with reflexive freedom (reason-based), and Law. This relationship is understood in the article as a tension that arises from the movement of pre-reflexive consciousness towards reflexive consciousness. The author also provides examples of legal issues that are affected by this understanding of the relationship between Law and freedom.
Keywords: pre-reflexive freedom; consciousness; phenomenology of law; spontaneous freedom; reflexive freedom